2013
DOI: 10.1016/j.immuni.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

miR-142-3p Prevents Macrophage Differentiation during Cancer-Induced Myelopoiesis

Abstract: Tumor progression is accompanied by an altered myelopoiesis causing the accumulation of immunosuppressive cells. Here, we showed that miR-142-3p downregulation promoted macrophage differentiation and determined the acquisition of their immunosuppressive function in tumor. Tumor-released cytokines signaling through gp130, the common subunit of the interleukin-6 cytokine receptor family, induced the LAP∗ isoform of C/EBPβ transcription factor, promoting macrophage generation. miR-142-3p downregulated gp130 by ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(121 citation statements)
references
References 57 publications
3
118
0
Order By: Relevance
“…For MDSCs and tumour-associated macrophages in solid tumours, a contextual regulation of C/EBPb activity favouring an immunosuppressive environment has been suggested 16,60 .…”
Section: Discussionmentioning
confidence: 99%
“…For MDSCs and tumour-associated macrophages in solid tumours, a contextual regulation of C/EBPb activity favouring an immunosuppressive environment has been suggested 16,60 .…”
Section: Discussionmentioning
confidence: 99%
“…(Sonda et al . (2013) identified 79 differentially expressed miRNAs in either tumor‐infiltrating versus normal CD11b + cells purified from the spleen of healthy mice. They found that miR‐142‐3p and miR‐150 were the most downregulated miRNAs in tumor‐infiltrating CD11b + cells and computationally determined genes that are involved in monocyte–macrophage commitment, as well as potential target genes of miR‐142‐3p (Sonda et al ., 2013).…”
Section: Transfer Of Biological Information Between Tumor Microenviromentioning
confidence: 99%
“…They found that miR‐142‐3p and miR‐150 were the most downregulated miRNAs in tumor‐infiltrating CD11b + cells and computationally determined genes that are involved in monocyte–macrophage commitment, as well as potential target genes of miR‐142‐3p (Sonda et al ., 2013). They further showed that miR‐142‐3p directly regulates gp130, which is a common subunit of the interleukin‐6 cytokine receptor family that regulates macrophage generation (Sonda et al ., 2013). A comprehensive list of extracellular miRNAs shuttling between cancer cells and their neighboring cells can be found in Table 1.…”
Section: Transfer Of Biological Information Between Tumor Microenviromentioning
confidence: 99%
“…The complete KO animals generated by us did not show any defects in numbers of HSCs when compared with WT animals (data not shown). Recent data have suggested a role for miR-142 in other hematopoietic-derived cell functions, such as regulatory T cell function (19), myeloid cell differentiation (9,12,13), and megakaryopoiesis (14). Furthermore, in association with other aberrations, it has also been incriminated in the development of hematopoietic malignancies (16,17) and even nonhematopoietic cells and malignancies (18,36).…”
Section: Upregulated Expression Of Atypical E2f7 and E2f8 In Mir-142 mentioning
confidence: 99%
“…miR-142 regulates innate immunity by negatively regulating IL-6 expression in DCs (9), and a recent study indicated that miR-142-3p plays critical roles in the maintenance of CD4 + DCs (12). Recent studies have also demonstrated that miR-142-3p prevents macrophage differentiation during tumor-induced myeloid differentiation (13) and megakaryopoiesis (14). But its role in adaptive immunity, specifically for naive T cell development and function, remains unknown.…”
Section: Introductionmentioning
confidence: 99%